Exploring Students’ Perceptions on Wayground: A Next-Generation Platform for English Proficiency Test - Pramudita, Rizqi Febrian; Dewangga, Vigo; Setyawan, Sunoko; Rinda, Renata Kenanga (Journal of Language, Communication, and Tourism, 2025)
The dynamic application of digital learning platforms, including innovative systems like Wayground, has significantly transformed the administration of English language tests such as the English Proficiency Test (EPT). As technology becomes increasingly integrated into educational environments, digital assessment tools are no longer optional but essential for supporting efficient and standardized testing practices. This study explores students’ perceptions of Wayground, a next-generation online platform used to conduct the EPT at Politeknik Negeri Jember. Using a quantitative approach, data were gathered from 217 students across nine departments through structured questionnaires. The results indicate that most respondents appreciate Wayground for its practicality, efficiency, and engaging user interface. Although some minor technical challenges were identified, the majority of participants expressed satisfaction with both the platform’s features and its exam supervision services. Overall, Wayground is viewed as a reliable, accessible, and user-friendly platform with strong potential to enhance digital transformation in English language assessment.  The future implementations of the English Proficiency Test should continue leveraging digital platforms like Wayground while simultaneously refining test content difficulty and strengthening technical and support infrastructures to ensure a more balanced, reliable, and equitable assessment experience for all participants.